2013
DOI: 10.3382/ps.2012-02843
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric plumage coloration produced by ovarian transplantation in chickens

Abstract: Ovaries from Rhode Island Red donors were transplanted orthotopically into White Leghorn recipients. At maturation, recipients were mated with Rhode Island Red roosters to test the origin of their ovaries, using plumage coloration as a marker. A chick with chimeric plumage coloration was produced, indicating mechanisms that produce follicles with both donor and recipient ovarian contents. This study suggests that ovarian transplantation could be useful for in vivo studies of cytological and molecular mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…A vitrification method that has been used in Japanese quail (Liu et al, 2013b) and chickens (Liu et al, 2013c) was adapted to ovaries from post-hatching turkey pouts with minimal modifications. Ovaries were put into fresh HM at room temperature (RT) and four ovaries (from four different poults) were transfixed on an acupuncture needle (J-type, Size No.…”
Section: Vitrification and Warming Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…A vitrification method that has been used in Japanese quail (Liu et al, 2013b) and chickens (Liu et al, 2013c) was adapted to ovaries from post-hatching turkey pouts with minimal modifications. Ovaries were put into fresh HM at room temperature (RT) and four ovaries (from four different poults) were transfixed on an acupuncture needle (J-type, Size No.…”
Section: Vitrification and Warming Proceduresmentioning
confidence: 99%
“…Techniques available to mammals, such as cryobanking of oocytes or embryos, have limited applicability for birds because of the structure of the avian egg ( Rothchild, 2003 ; Hagedorn, 2006 ). Alternatively, the ovarian tissue can be cryopreserved and recovered by orthotopic transplantation, which has been achieved in Japanese quail and chickens ( Liu et al , 2010 ; 2013b , c ) and used to preserve specialized lines in these species ( Silversides et al , 2013 ). The essentiality of extrapolating this model to the domestic turkey, another important poultry species and model organism ( Moore and Siopes, 2004 ; Aslam et al , 2012 ), appears obvious.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical procedures used for ovariectomy of 1-day-old chickens [20] were adapted for castration of 1-wk-old quail. Recipient WB chicks were anesthetized by administration of isoflurane gas.…”
Section: Testicular Allograftingmentioning
confidence: 99%
“…This technique has been successfully used to produce live offspring from fresh ovarian transplants in chickens (Song and Silversides, 2007b), Japanese quail (Song and Silversides, 2008a) and ducks (Song et al, 2012) and from cryopreserved ovarian transplants in Japanese quail (Liu et al, 2010). We have recently improved this technique by making a smaller cut parallel to the median plane on the left side of the abdominal cavity of the recipients to expose the ovary without externalising the gizzard and intestines (Liu et al, 2013a). In addition, Karagenç et al (2011) demonstrated that survival of two-day old recipients is better than one-day old recipients and we now conduct the transplantation in older chicks which significantly reduces mortality during surgery and simplifies the technique by eliminating the need to remove the yolk sac (unpublished data).…”
Section: Transplantation Of Avian Gonadal Tissuementioning
confidence: 99%